A sandwich-type photoelectrochemical aptasensor using Au/BiVO4 and CdS quantum dots for carcinoembryonic antigen assay. Issue 19 (1st September 2021) - Zhou, Nan; Xu, Xiaofan; Li, Xi; Yao, Wengao; He, Xiaohang; Dong, Yulin; Liu, Dan; Hu, Xiaosong; Lin, Yawei; Xie, Zhizhong; Qu, Deyu; Zhang, Chaocan
Abstract : A sandwich-type PEC aptasensor based on Au/BiVO4 and CdS QDs exhibits a high detection performance for CEA due to LSPR and RET. Abstract : A novel sandwich-type photoelectrochemical (PEC) aptasensor for the carcinoembryonic antigen (CEA) assay was fabricated using the CEA aptamer, Au/BiVO4 and CdS quantum dots (CdS QDs). In virtue of the localized surface plasmon resonance effect of Au nanoparticles, Au/BiVO4 showed an effective utilization of visible light and excellent photoactivity, and was employed as the photoanode. After CdS QDs were conjugated to Au/BiVO4 through the sandwich structure based on the hybridization of the CEA aptamer with two partially complementary single-stranded DNA molecules, the photocurrents were further enhanced by a resonance energy transfer between CdS QDs and Au nanoparticles. Meanwhile, the consumption of the photo-induced holes by ascorbic acid could also retard the combination of the electron–hole pairs and cause an increase of the photocurrents. However, the specific recognition of CEA by the CEA aptamer could destroy the sandwich structure and remarkably weaken the photocurrent response. Thus, the quantitative detection of CEA was connected with the decrease of the photocurrent. Benefitting from the above methods for signal enhancement, the PEC aptasensor showed a wide sensing range of 0.0001–10 ng mL −1 and a low detection limit of 0.047 pg mL −1 for CEA detection. The specificity, stability and recoveries of the PEC aptasensor were also excellent. Therefore, the construction of the present PEC aptasensor provides a universal and practical method for sensing other substances.